Pelatihan Pembuatan Arang Aktif dari Sekam Padi untuk Penjernihan Minyak jelantah sebagai Bekal Wirausaha Masyarakat - Mulyani, Sri; Ciptonugroho, Wirawan; Wathon, Muhammad Hizbul; Shidiq, Ari Syahidul (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
Most of the area in Jabung Village, Pelupuh, Sragen is paddy fields, with most of the population's livelihood being farm workers and convection business. However, during the Pandemic, the convection business was sluggish and slumped. This makes the people of Jabung village need other alternative businesses to increase their income. The amount of agricultural land in Jabung village, which produces rice husk waste, can be an alternative for new businesses for the community. Based on the research results of the Research Group (RG) at the Chemistry Education Study Program, UNS, rice husks can be made as activated charcoal, which is used to purify used cooking oil. The purified cooking oil can be used to make biodiesel, soap and aromatherapy candles. Therefore, the community service team of the Chemistry Education Study Program has provided training on the manufacture of activated charcoal from rice husks and its use for purifying used cooking oil as a provision for business in Jabung Village. Attended by 60 participants, this training focused on three main activities; educating the community about the process of absorption by activated charcoal, purifying used cooking oil using activated charcoal from rice husks, and marketing processed products from used cooking oil and activated charcoal. The results of the evaluation of this training, as many as 36.73% of participants strongly agree, and 53.06% agree that the community gets direct benefits from training activities on making activated charcoal from rice husks and its use for cleaning used cooking oil.